RIBA DALAM AL-QURAN: SEBUAH KAJIAN ANTROPOLOGIS - dkk., Ahmad Muzhaffar (UIN Sunan Kalijaga Yogyakarta, 2015)
This article examines the concept of riba in the Qur'an. It was conducted by reviewing the texts of the Koran which speak of usury and explore the practice of usury in Arab society at the time of the Qur'an was revealed. Al-Quran through the teachings contained in it trying to organize traditions prevailing in Arab society. In this case, there are three stages that used by the Qur'an in the process of structuring the tradition, namely the adoption, adaptation, and integration. In the first stage (adoption), the Qur’ran pay attention traditions already in force as well as practice in the life of Arab society. at this stage, sometimes Qur'an appreciate the traditions of Arab society, but sometimes criticize or even question the existence of the tradition of the Arab community itself. While the adoption phase generally begins with a dialogue about the benefits and unbenenif of tradition. The integration phase is done by growing social awareness of Arab society against their own habit. If the observed association (absurd) between verses usury with those before and after, then it can be known that usury is the antithesis to charity. In charity, the rich gave most wealth to sympathize needs of the poor and the indigent, the usury contrary, retrieve, exploit, and even the